DS-ADMM++: A Novel Distributed Quantized ADMM to Speed up Differentially Private Matrix Factorization - Zhang, Feng; Xue, Erkang; Guo, Ruixin; Qu, Guangzhi; Zhao, Gansen; Zomaya, Albert Y. (IEEE transactions on parallel and distributed systems, 2022)
Matrix factorization is a powerful method to implement collaborative filtering recommender systems. This article addresses two major challenges, privacy and efficiency, which matrix factorization is facing. We based our work on DS-ADMM, a distributed matrix factorization algorithm with decent efficiency, to achieve the following two pieces of work: (1) Integrated local differential privacy paradigm into DS-ADMM to provide the privacy-preserving property; (2) Introduced a stochastic quantized function to reduce transmission overheads in ADMM to further improve efficiency. We named our work DS-ADMM++, in which one '+' refers to differential privacy, and the other '+' refers to quantized techniques. DS-ADMM++ is the first to perform efficient and private matrix factorization under the scenarios of differential privacy and DS-ADMM. We conducted experiments with benchmark data sets to demonstrate that our approach provides differential privacy and excellent scalability with a decent loss of accuracy.